PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN RAMANIA (Bouea macrophylla Griffith) TERHADAP PENURUNAN KADAR GULA DARAH MENCIT PUTIH (Mus muscullus) YANG DIINDUKSI ALOKSAN - Eka Kumalasari; Yugo Susanto; Maulida Yulia Rahmi; Dwi Rizky Febrianty (JCPS (Journal of Current Pharmaceutical Sciences), 2019)
Diabetes mellitus is the disease of impaired metabolism that results when the pancreas does not produce enough insulin or when no body can effectively use insulin produced so as to cause an increased concentration of blood glucose. The treatment of diabetes mellitus can be an injection and tablet form which could result in the use of long term side effects. prevent it can use alternative treatment using Bouea macrophylla. Ramania is plants typical of South Kalimantan, active ingredients that is flavonoid and saponin which was is one of a substance efficacious as antidiabetic. This research from pre and post test with control group desain. Totaled white mice (Mus musculus) male to be used is 25 mices, devided into 5 groups is control negative (CMC Na 0,5%), control positif (Glibenklamid 3 mg/kgBB), extract 125 mg/kgBB, 250 mg/kgBB and 500 mg/kgBB. Observation agains in lowering blood glucose levels each groups test done on the day 7th and 14th after hiperglikemia induced by alloxan. Data the results of the analysis General Linear Model show that extract can in lowering blood glucose levels on white mice male that induced by alloxan significantly p<0,05. Doses of extract most effective in lowering blood glucose levels mice is 500 mg/kgBB.